Diálogos sobre gênero e sexualidade com professores de uma escola da rede estadual de ensino - Silva, Francisco Henrique Cardoso da (2023)
Discussions about gender and sexualities are the most exponent today, considering the claims of the most varied expressions that we can perceive in society, since many socially invisible groups resist the oppressions that their bodies have historically been subjected to. Gender and sexuality are approached based on queer theory and Foucauldian studies. Gender is a relatively recent social construction, from which it is understood the need to question the social roles and expectations of behavior between the feminine and masculine. Sexuality is not a given of nature, but the name of a historical device, demarcated in the period of the mid-18th century. This device speaks of a network braided by a set of practices, discourses and techniques for stimulating bodies, intensifying pleasures and building knowledge. The general objective of the research is to build a training course on gender and sexuality with teachers from state schools. As specific objectives: to promote spaces and discussions in the school environment on gender and sexuality issues; identify the discourses attributed to genders and sexualities in the school culture and understand the expressions of gender and sexuality in the LGBTQIAP+ school context. Methodologically, in this way, the research will be focused on qualitative studies with the orientation of the Socioanalysis perspective, it turns to a more sociological and political bias of the institutional work, perceiving the institution as an integrated system of definitions in relation to the social reality and about behaviors, assigning them values. Socioanalysis aims to carry out interventions aimed at building tools that can help the group in its self-management process, that is, it envisions group autonomy. The context in which the research was carried out is a full-time state public school, located in the municipality of Crateús in Ceará. Located on the outskirts of the city, which has 350 students and 34 professors. The school operates in three shifts with classes from the 1st to the 3rd year of high school, with only the 1st year working fully. The meetings were articulated based on conversation circles, with the proposal being to foster a space for exchanging knowledge that revolves around gender and sexuality themes. At each meeting, a device that generated discussions was built together with the teachers. In this perspective, the field diary was used as a data collection instrument. From the implementation of the research, the teachers felt more theoretically equipped to manage, work and feel safe with the expressions of genders and sexualities. It is believed that there have been changes in the reception of LGBTQIAP+ students in a more satisfactory way, teachers who are more aware of the demands of the LGBTQIAP+ population, recognition of demands, needs, resources and potential. Coherence of gender and sexuality discussions at school, the strengthening of plural, cultural, affective and sexual knowledge. The products of this research were a technical report and a booklet with the methodology of the training process.